2015
DOI: 10.3390/ijms161025516
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of DXS and DXR Genes in the Terpenoid Biosynthetic Pathway of Tripterygium wilfordii

Abstract: 1-Deoxy-d-xylulose-5-phosphate synthase (DXS) and 1-deoxy-d-xylulose-5-phosphate reductoisomerase (DXR) genes are the key enzyme genes of terpenoid biosynthesis but still unknown in Tripterygium wilfordii Hook. f. Here, three full-length cDNA encoding DXS1, DXS2 and DXR were cloned from suspension cells of T. wilfordii with ORF sizes of 2154 bp (TwDXS1, GenBank accession no.KM879187), 2148 bp (TwDXS2, GenBank accession no.KM879186), 1410 bp (TwDXR, GenBank accession no.KM879185). And, the TwDXS1, TwDXS2 and Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…There are at least two ways in which the biosynthesis of terpenoids can be regulated: (1) at the level of terpenoid backbone biosynthesis and (2) at the level of substrates for TPSs. Previous studies have suggested that in the terpenoid backbone biosynthesis pathway, the rate of metabolic flux through the MEP pathway is controlled by DXS and DXR [29]. Furthermore, DXS and HDR are encoded by small gene families; there are three functional DXS genes in maize [31] and two different HDR genes in Pinus taeda [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are at least two ways in which the biosynthesis of terpenoids can be regulated: (1) at the level of terpenoid backbone biosynthesis and (2) at the level of substrates for TPSs. Previous studies have suggested that in the terpenoid backbone biosynthesis pathway, the rate of metabolic flux through the MEP pathway is controlled by DXS and DXR [29]. Furthermore, DXS and HDR are encoded by small gene families; there are three functional DXS genes in maize [31] and two different HDR genes in Pinus taeda [32].…”
Section: Discussionmentioning
confidence: 99%
“…In the MEP pathway, one DXS (1-deoxy-D-xylulose-5-phosphate synthase) and two DXR (1-deoxy-D-xylulose-5-phosphate reductoisomerase) genes were down regulated in MC-DF vs MC-RF. Also, DXS and DXR may play rate-limiting roles in controlling metabolic flux through the MEP pathway [29]. A previous study reports that DXS and HDR are both encoded by small gene families in higher plants, and influence the accumulation of downstream isoprenoids [30].…”
Section: Identification Of Degs and Further Analysis Of The Terpenoidmentioning
confidence: 99%
“…Based on previous reports [55,56], we speculate the expression levels of dioscin in different tissues of D. opposita may be different and are related to key enzymes of the biosynthetic pathway. Therefore, to explore the dioscin accumulation and translocation in leaf and rhizome tissues, we compared the differentially expressed genes (DEGs) and elementary identi ed terpene biosynthetic genes through the RNA-seq, which would lay a foundation to study the terpenoids biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, there are three DXS genes encoding functional enzymes in maize ( Zea mays ), and two different genes encoding HDR have been identified in loblolly pine ( Pinus taeda ) [34,35]. Furthermore, previous studies have suggested that DXS and DXR have rate-limiting roles when controlling the metabolic flux through the MEP pathway [36]. Recently, the genetic transformation of Artemisia annua enhanced the biosynthesis of artemisinin by overexpressing DXR gene [37].…”
Section: Introductionmentioning
confidence: 99%